THE MARKETING ANALYSIS AS THE MECHANISM OF INCREASE IN COMPETITIVE ADVANTAGES OF THE ENTERPRISE IN THE BRANCH MARKET - L. Putyatina; O. Orlova; L. Lavrova (Вестник университета, 2017)
In article it is proved that the main directions of marketing activity of the enterprises in modern economy combine lines of economic, financial, planned, production, marketing and research work. In the general structure of marketing by authors marketing of research and development, marketing of goods and services, marketing of means of production, marketing of material resources, import and export marketing, marketing of financial and investment activity, marketing of social development is allocated.